Analisis Daya Serap Air dan Sensori Sarut dengan Variasi Heat Moisture Treatment Pati Sagu - Picauly, Priscillia; Tetelepta, Gilian (Universitas Pattimura, 2025)
Sarut is one of the traditional snacks of Maluku, which has a slightly hard texture characteristic. The purpose of this study was to analyze the effects of native and heat moisture treatment (HMT) sago starch treatments on water absorption and sensory properties of sarut sticks compared to the commercial ones. The study used a completely randomized design with one factor: native sago starch and HMT sago starch at 24%, 27%, and 30%. Three replications were used. The results showed that sarut with native and HMT sago starch treatments had low water absorption (159.95%-171.88%) and were preferred in terms of color, aroma, taste, texture, and overall compared to commercial sarut.